Lifestyle patterns associated with common mental disorders in Brazilian adolescents : results of the Study of Cardiovascular Risks in Adolescents (ERICA) - Silva, Sara Araújo da (2021)
The association between lifestyle factors and mental health has been evaluated in isolation; however, there has been a lack of information about lifestyle patterns and Common Mental Disorders (CMD) in adolescents. Therefore, the present study aims to assess the associa tion between sets of lifestyle patterns and the occurrence of CMD in Brazilian adolescents evaluated in a national school-based cross-sectional survey. The outcome variable consid ered was presence of CMD. Lifestyle patterns were identified from the Principal Component Analysis. Consumption of foods, water and alcoholic beverages, sleep, physical activity, and smoking were used to identify patterns as explanatory variables. Sociodemographic characteristics, administrative dependence of the school and, nutritional status, were considered adjustment factors in the regression model. A total of 70,427 adolescents were evaluated. The principal component analysis identified three lifestyle patterns: high consumption of ultra-processed foods and low consumption of unprocessed or minimally processed foods (pattern 1); high consumption of alcoholic beverages and tobacco in the last 30 days (pattern 2); and high consumption of water and high level of physical activity (pattern 3). In the adjusted model, in patterns 1 and 2, the third tertile presented greater chance of CMD (OR 1.68; CI 95% 1.51–1.87 and OR 1.38; CI 95% 1.19–1.60, respectively). In pattern 3, the second (OR 0.88; CI 95% 0.80–0.96) and the third (OR 0.80; CI 95% 0.72–0.88) tertiles presented lower chances of CMD among the adolescents evaluated. There fore, we suggest that health-promoting practices aimed at adolescents include multiple behaviors, with the objective of ensuring physical, mental, and social well-being.